The Effectiveness of Cassava Leaf (Manihot esculenta C.) Flavonoid Quercetin as Dengue Virus-1 Antivirus in Vitro - Rayasari, Husnaya; Apriyanto, Dadan Ramadhan; Brajawikalpa, Rama Samara; Dewi, Beti Ernawati (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Dengue fever is a mosquito-borne disease that can cause severe symptoms and death, placing high burden on healthcare systems in tropical regions. Currently, there are no antiviral treatments. It has been proven that synthetic quercetin able to improve body performance and reduce the risk of infection as well as inhibit DENV replication. Cassava leaves (Manihot esculenta C.) contain anthocyanins (flavonoids) such as quercetin and it shows potential as antiviral agent as the synthetic as well. Aims: To describe the levels of self-compassion and procrastination among medical students and to examine how these factors relate to academic performance. Methods: This experimental study used post-test only with control group design consisted of 13 treatment groups and 1 control group. Treatment group were divided into 6 different concentrations for inhibition test (50 µg/mL, 25 µg/mL, 12.5 µg/mL, 6.25 µg/mL, 3.125 µg/mL, 1.5 µg/mL) and 7 different concentrations for cytotoxicity test (80 µg/mL, 40 µg/mL, 20 µg/mL, 10 µg/mL, 5 µg/mL, 2.5 µg/mL, 1.25 µg/mL). The control group was a negative control treated with 0.2% DMSO. Inhibition was assessed by Focus Forming Unit Assay and cytotoxic was assessed by number of Microtiter Tetrazolium Assay (MTT Assay). The statistical analysis used in this study were the Shapiro-Wilk test for normality test, Kruskal-Wallis test for hypothesis test, and post-hoc test to determine whether the groups studied in this research had significant differences from each other. Results: The CC50 and IC50 values of quercetin of cassava leaf (Manihot esculenta C.) were found to be 3.44 μg/mL and 0.25 μg/mL, respectively, with an SI value of 123. Based on these results, it can be concluded that the flavonoid quercetin of cassava leaf (Manihot esculenta C.) exhibits selective properties in inhibiting the replication of DENV-1. Statistical analysis showed non-normal distribution (P<0.05), hypothesis test was accepted (P<0.05), and no significant differences between concentrations in the post-hoc test. Conclusion: Quercetin of cassava leaf (Manihot esculenta C.) is effective as an antiviral agent against dengue serotype 1 strain New Guinea C in vitro. Received: 25 September 2024 | Reviewed: 15 October 2024 | Revised: 30 November 2024 | Accepted: 15 December 2024. Dimension Badges: